Osteogenic and Adipogenic Differentiation of Mesenchymal Stem Cells in Gelatin Solutions of Different Viscosities. Issue 23 (5th August 2020) - Lee, Kyubae; Chen, Yazhou; Yoshitomi, Toru; Kawazoe, Naoki; Yang, Yingnan; Chen, Guoping
Abstract: Accumulating evidence indicates that stem cell fate can be regulated by mechanical properties of the extracellular matrix. Most studies have focused onthe influence of matrix elasticity and viscoelasticity on stem cell differentiation. However, how matrix viscosity affects stem cell differentiation has been overlooked. In this study, a biphasic gelatin solution/hydrogel system is used for 3D culture of human bone marrow–derived mesenchymal stem cells (MSCs) to investigate the influence of gelatin solution viscosity on simultaneous osteogenic and adipogenic differentiation at the same culture condition. Gelatin solution promotes cell proliferation, while its promotive effect decreases with the increase of viscosity. The influence of viscosity on osteogenic and adipogenic differentiation of MSCs shows opposite trends. A high‐viscosity gelatin solution results in an increase of alkaline phosphatase (ALP) activity, calcium deposition, and expression of osteogenesis‐related genes. On the other hand, in a low‐viscosity gelatin solution, a lot of lipid vacuoles are formed and adipogenesis‐related genes are highly expressed. The results indicate high viscosity is beneficial for osteogenic differentiation, while low viscosity is beneficial for adipogenic differentiation. These findings suggest the importance of matrix viscosity on stem cell differentiation in 3D microenvironments. Abstract : A 3D biphasic gelatin solution/hydrogel system is used to investigate the influence of solution viscosity on balancing osteogenic and adipogenic differentiation of mesenchymal stem cells (MSCs). The differentiation of MSCs in gelatin solutions is dependent on their viscosities. High viscosity is beneficial for osteogenic differentiation while low viscosity for adipogenic differentiation.